2016
DOI: 10.1021/acs.est.6b00877
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Bisphenol A in Terrestrial and Aquatic Environments

Abstract: Bisphenol A (2,2-bis[4-hydroxyphenyl]propane, BPA), the monomer used to produce polycarbonate plastic and epoxy resins, is weakly estrogenic and therefore of environmental and human health interest. Due to the high production volumes and disposal of products made from BPA, polycarbonate plastic and epoxy resins, BPA has entered terrestrial and aquatic environments. In the presence of oxygen, diverse taxa of bacteria, fungi, algae and even higher plants metabolize BPA, but anaerobic microbial degradation has no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(111 citation statements)
references
References 219 publications
4
89
0
Order By: Relevance
“…In addition, the photocatalytic oxidation activities of alloys also be investigated and Bisphenol A (BPA) was as the model target compound. BPA is a relatively recalcitrant endocrine disruptor that is commonly detected in water . As shown in Figure b, all the alloys exhibited better photocatalytic oxidation activity than BiOCl and BiOBr.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, the photocatalytic oxidation activities of alloys also be investigated and Bisphenol A (BPA) was as the model target compound. BPA is a relatively recalcitrant endocrine disruptor that is commonly detected in water . As shown in Figure b, all the alloys exhibited better photocatalytic oxidation activity than BiOCl and BiOBr.…”
Section: Resultsmentioning
confidence: 96%
“…BPA is a relatively recalcitrant endocrine disruptor that is commonly detected in water. [47] As shown in Figure 7b, all the alloys exhibited better photocatalytic oxidation activity than BiOCl and BiOBr. Among the alloys, BiOCl 0.72 Br 0.28 was also more effective for BPA degradation, removing 96.5 % of BPA upon visible light irradiation for 6 h (compared to 67.6 % for irradiated BiOCl 0.23 Br 0.77 and 34.1 % for irradiated BiOCl 0.48 Br 0.52 ).…”
Section: Photocatalytic Applicationsmentioning
confidence: 84%
“…urine, blood, saliva) from the majority of people living in developed nations. 13 Such ubiquitous BPA exposure is concerning, as BPA is a known estrogen mimic and endocrine disruptor. 14 15 Regulatory changes and consumer-driven pressure over the health effects of BPA have caused companies to replace BPA with other bisphenols (BPs), such as bisphenol S (BPS, compound 2) and bisphenol F (BPF, compound 3).…”
Section: Introductionmentioning
confidence: 99%
“…While the potential exists for degradation of environmental BPA through hydrolysis or photolysis, the quantity of BPA eliminated through degradation in pure water is not significant 4,20,21 . Rather degradation occurs only in the presence of humic substances, due to reactive oxygen species found in conjunction with humic substances 22 .…”
mentioning
confidence: 99%
“…Rather degradation occurs only in the presence of humic substances, due to reactive oxygen species found in conjunction with humic substances 22 . A previous study found the half-life of BPA in surface water ranged from 66 hours to 160 days from photolytic degradation, due to water condition variation 4 . Further, the degradation observed over 160 days did not prevent BPA from traveling through the water system and harming aquatic organisms 4 .…”
mentioning
confidence: 99%